2002
DOI: 10.1038/sj.onc.1205406
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of mitochondrial DNA-deficient cells to TRAIL: role of Bax in TRAIL-induced apoptosis

Abstract: Mitochondrion is one of the master players in both apoptosis and necrosis. We studied the role of mitochondrial function in TRAIL-induced apoptosis. TRAIL killed SK-Hep1 cells with characteristic features of apoptosis such as DNA fragmentation, sub-G1 ploidy peak and cytochrome c translocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 55 publications
8
58
2
Order By: Relevance
“…However, most 0 cells have been reported to undergo apoptosis as efficiently as their parental cells (4 -6). In contrast, we have reported that mtDNA-depleted hepatoma cells (SK-Hep1 0 cells) are resistant to TRAIL-induced apoptosis, which is consistent with the importance of mitochondria in cell death (7). However, it is not clearly elucidated how those cells with mitochondrial dysfunction resist cell death.…”
contrasting
confidence: 43%
“…However, most 0 cells have been reported to undergo apoptosis as efficiently as their parental cells (4 -6). In contrast, we have reported that mtDNA-depleted hepatoma cells (SK-Hep1 0 cells) are resistant to TRAIL-induced apoptosis, which is consistent with the importance of mitochondria in cell death (7). However, it is not clearly elucidated how those cells with mitochondrial dysfunction resist cell death.…”
contrasting
confidence: 43%
“…Cell lines were examined for expression of proapoptotic Bax protein, which has been reported to be required for TRAIL-mediated apoptosis in some cell lines. 52,53 All cell lines we tested expressed substantial amounts of Bax (Fig 6), and again no correlation was found between relative Bax levels and TRAIL sensitivity.…”
Section: Death Ligand Gene Therapy Of Brain Tumor Cells S Rubinchik Ementioning
confidence: 86%
“…15,16 Others have shown that Bid can block the inhibitory effect of Bcl-2 on Fas-mediated apoptosis of HCC cells through oligomerizing Bak to release cytochrome c. 17 In SK-HEP-1 cells, TNF-related apoptosis-inducting ligand is known to induce the translocation of Bax, which subsequently leads to the cleavage of Bid. 18 Bid also has important functions in the development and chemotherapeutic sensitivity of HCC. Our previous experiments have shown that the level of Bid decreased in HCC tissues of patients except in poorly differentiated HCC in which cells may undergo a process of apoptosis or necrosis.…”
Section: Introductionmentioning
confidence: 99%